2009
DOI: 10.1007/s11172-009-0295-9
|View full text |Cite
|
Sign up to set email alerts
|

Debenzylation of 2,6,8,12-tetraacetyl-4,10-dibenzyl-2,4,6,8,10,12-hexaazatetracyclo[5.5.0.03,11.05,9]dodecane

Abstract: The debenzylation of 2, 6,8,12 tetraacetyl 4,10 dibenzyl 2,4,6,8,10,12 hexaazatetra cyclo[5.5.0.0 3,11 .0 5,9 ]dodecane by catalytic hydrogenolysis in a mixture of HСООH with other RCOOH (R = Me, Et, Pr i ) is accompanied by the N formylation of the liberated secondary amino groups. The alkaline hydrolysis of the obtained products makes it possible to remove the formyl groups with the retention of the acetyl groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Synthetic methods for tetraacetyl hexaazaisowurtzitane ( III ) are commonly known and industrially employed. A cascade condensation of benzylamine with glyoxal furnished hexabenzyl hexaazaisowurtzitane ( V ). Two-stage hydrogenation of V over the Pd catalyst produced VI (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Synthetic methods for tetraacetyl hexaazaisowurtzitane ( III ) are commonly known and industrially employed. A cascade condensation of benzylamine with glyoxal furnished hexabenzyl hexaazaisowurtzitane ( V ). Two-stage hydrogenation of V over the Pd catalyst produced VI (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Synthetic methods for tetraacetyl hexaazaisowurtzitane ( III ) are commonly known and industrially employed. 23 24 25 A cascade condensation of benzylamine with glyoxal furnished hexabenzyl hexaazaisowurtzitane ( V ). A twostage hydrogenation of V over Pd catalyst produced VI (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…In order to eliminate the step of isolation of crystalline TADB from the solution in acetic acid, conduction of the second debenzylation step in a mixture of formic and acetic acids was proposed. 626 A TEM study of catalyst samples demonstrated that in the repeated use of the catalyst, palladium particle size considerably increases and, hence, the active metal surface area decreases. The coarsening of palladium particles in both the first and second debenzylation steps occurs from one cycle to another to reach a definite threshold value after which the catalyst completely loses activity.…”
Section: Scheme 149mentioning
confidence: 99%